THE EFFECT OF GAME-BASED LEARNING MODEL ASSISTED BY A BAMBOOZLE ON THE MULTIPLICATION OPERATION SKILLS OF ELEMENTARY SCHOOL STUDENTS - Irma Retno Rahayu; Diki Rukmana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Skills in solving multiplication operations are categorized as very low for second- grade elementary school students. The purpose of the research in this article is to determin the effect of the game-based learning model assisted by